The BRASH syndrome, a synergistic arrhythmia phenomenon - Grigorov, Mladen V. (Proc (Bayl Univ Med Cent), 2020)
BRASH syndrome is a relatively novel clinical entity with profound bradycardia secondary to simultaneous metabolic derangement and drug toxicity. The syndrome is a clinical pentad of bradycardia, acute kidney injury, use of atrioventricular nodal blocking agents, shock, and hyperkalemia. It is widely underrecognized with selectively few reports, mainly in the elderly population. We present a 43-year-old woman on two oral atrioventricular blocking agents who presented with 1 week of increasing lethargy with rapid deterioration into cardiac arrest with subsequent shock postresuscitation. She was found to have hyperkalemia, metabolic acidosis, and acute kidney injury on arrival. Her initial electrocardiogram was remarkable for sinus arrest and junctional bradycardia. She was treated with a temporary pacemaker, renal replacement therapy, and potassium-lowering agents, with subsequent improvement resulting in conversion to normal sinus rhythm.